Pengaruh keragaman produk, harga dan lokasi terhadap keputusan berbelanja di Smartshop Marelan - Nabilah Siregar; Sinto; Syamsul Bahri Subakti (Fakultas Ekonomi Universitas Al-Azhar Medan, 2026)
This study aims to examine the influence of product diversity, price and location on shopping decisions at Smartshop Marelan. The study method used in this study is quantitative in character. The data collection techniques used are observation, documentation studies and questionnaires. Through this study, because the population in this study is not aware of its quantity, the Lemeshow formula is used to determine the total sample. So, the grand total participants in this study are 96 customers. The results of the study indicate that partially product diversity has a positive and prominent effect on shopping decisions at Smartshop Marelan with a t-count value> t-table (3.335> 1.9860) and stands out by 0.001 smaller than 0.05. Price has a positive and prominent effect on shopping decisions at Smartshop Marelan with a t-count value> t-table (2.792> 1.9860) and stands out by 0.006 smaller than 0.05. Location has a positive and prominent influence on shopping decisions at Smartshop Marelan with a t-count value > t-table (2.568 > 1.9860) and a prominence of 0.012 smaller than 0.05. Simultaneously, the results of the study show that product diversity, price and location together influence shopping decisions at Smartshop Marelan with a Fcount value (64.855) > Ftable (2.70), and a prominence value of 0.000 < 0.05